Endothelin-1 Expression Associated with Lipid Peroxidation and Nuclear Factor-κB Activation in Type 2 Diabetes Mellitus Patients with Angiopathy and Limb Amputation. Issue 1 (January 2016) - Kuo, Yur-Ren; Chien, Ching-Ming; Kuo, Ming-Jen; Wang, Feng-Sheng; Huang, Eng-Yen; Wang, Ching-Jen
Abstract : Background: It is unclear whether diabetic angiopathy is related to oxidative stress-associated endothelial dysfunction. The authors investigated whether alteration of endothelin-1 and lipid peroxide production and activation of nuclear factor-κB expression were involved in lower limb amputation in type 2 diabetes mellitus patients. Methods: A total of 135 subjects including 51 type 2 diabetes mellitus patients with major lower extremity amputations and 36 diabetes mellitus patients without limb and vascular complication and 48 normal controls were recruited for this study. The authors measured the plasma soluble endothelin-1 concentrations by a sandwich enzyme immunoassay, and measured oxidative stress as determined by the lipid peroxide byproduct malondialdehyde. Histologic staining and nuclear factor-κB activation determined by electrophoretic mobility shift assay of the amputated vessels were examined. Results: Histologic staining revealed that severe arteriosclerosis with atheroma formation in the amputated diabetic arteries was significantly prominent compared with normal controls. Soluble endothelin-1 concentrations and malondialdehyde levels were increased significantly in diabetic amputation patients compared with other groups ( p < 0.001). The nuclear factor-κB binding activity in amputated diabetic stump vessels was more prominent compared with healthy vessels without diabetes mellitus. There was a positive correlation between endothelin-1 and malondialdehyde in patients with diabetic amputation ( r = 0.46, p = 0.001). Conclusions: These results suggest that elevation of endothelin-1 and lipid peroxide levels is involved in the pathogenesis of diabetic foot amputation. An increase of lipid peroxide and endothelin-1 associated with nuclear factor-κB activation plays an important role in the development of diabetic angiopathies.